Analisis Semiotika Video Edukasi Darurat Eksploitasi Anak - Purwanto, Farelino Arsyi Vernanda; Widyasari; Wibisono , Aryo Bayu (Kaisa: Jurnal Pendidikan dan Pembelajaran, 2025)
Exploitation of children under the age of 13 in Indonesia is a serious social problem, covering economic, sexual and social exploitation. This research aims to design an educational video titled "Emergency Child Exploitation" that uses visual media, particularly videography, as an effective communication tool to raise public awareness. The approach used in this research is a semiotic analysis of the visual and narrative elements in the video. Through Roland Barthes' semiotic theory, the video is analyzed to reveal the denotative and connotative meanings contained in symbols, colors, gestures, sounds, and other visual elements. The results of the analysis show that the semiotic elements in this video, such as children playing, scavengers, and crowded streets, provide deep meanings about freedom, economic inequality, and the pressures of urban life. This research not only produces a video as a social campaign tool, but also enriches academic studies in visual communication studies. This educational video is expected to be an effective tool in building public awareness and reducing child exploitation through a meaningful visual approach.